Environmental hydraulics of open channel flows - Chanson, Hubert
Environmental Hydraulics is a new text for students and professionals studying advanced topics in river and estuarine systems. The book contains the full range of subjects on open channel flows, including mixing and dispersion, Saint-Venant equations method of characteristics and interactions between flowing water and its surrondings (air entrainment, sediment transport). Following the approach of Hubert Chanson's highly successful undergraduate textbook Hydraulics of Open Channel Flow, the reader is guided step-by-step from the basic principles to more advanced practical applications. Each section of the book contains many revision exercises, problems and assignments to help the reader test their learning in practical situations. Complete text on river and estuarine systems in a single volume Step-by-step guide to practical applications Many worked examples and exercises.